Physiotherapy interventions for people with dementia and a hip fracture—a scoping review of the literature. Issue 4 (December 2017) - Hall, A.J.; Lang, I.A.; Endacott, R.; Hall, A.; Goodwin, V.A.
Abstract: Background: People with dementia are 2.7 times more likely to suffer a hip fracture than those without and their management is estimated to cost £0.92 billion per year. Yet there has been little focus on the effectiveness of interventions for this population. Objective: The aim of this scoping review was to summarise the current available evidence for physiotherapy interventions for people with dementia who fracture their hip as well as to identify gaps in the literature that may require further research. Data sources: A systematic search of the following databases was undertaken—TRIP, CINAHL, Amed, Embase, PEDro, PsycINFO, Cochrane Library, Open Grey, Ethos, ISRCTN, Proquest, PROSPERO and UK Clinical Trials Gateway. Study selection: Articles were included if they described an intervention which is considered within the scope of a physiotherapist and targeted those with both a hip fracture and dementia. Synthesis methods: A narrative summary was then undertaken to describe the current state of the literature. Results: Twenty six studies were included, of which thirteen were observational, six RCTs, two qualitative, two surveys and three systematic reviews. Only nine studies focused explicitly on physiotherapy interventions. Conclusion: The findings of this scoping review suggest there is limited evidence to guide physiotherapists in the management of people with dementia who fracture their hip. No evidence was found about perceptions or experiences of patients in this group or of the physiotherapists involved in their care. Further research is needed to develop and evaluate physiotherapy interventions for people with dementia who fracture their hip.